MODELING OF THE HYDRAULIC PERFORMANCE OF OGEE SPILLWAY USING COMPUTATIONAL FLUID DYNAMICS (CFD) - MOHAMMED, JOWHAR R.; NOORI, BAHZAD M. A.; HUSSEIN, IHSAN A. (Journal of Duhok University, 2017)
Computational fluid dynamics (CFD) is a type of numerical modeling that is used to solve problems involving fluid flow. Since CFD can provide faster and more economical solution than physical modeling, hydraulic engineers are interested in verifying the capability of CFD software. This study has examined the ability of the commercial CFD software (Flow-3D) to model an ogee-crested spillway by making data comparisons to physical models (experimental data). Three spillway models of different heights (20cm, 25cm, and 30cm) were fabricated and tested for design heads of (5cm, 7cm, 10cm), respectively. The study was conducted to compare flow parameters over a standard ogee-crested spillway using physical and numerical models. The physical models were fabricated from a rigid foam and placed in a test flume. Pressure taps were installed along the entire length of the spillways. Water surface profiles and pressure data were recorded for five different flow conditions (1.2Hd, 1Hd, 0.75Hd, 0.5Hd, and 0.25Hd). The results of this study showed that there were good agreements between the results of physical and numerical models for water surface profiles and there were some discrepancies in pressure results.